Long-Term Trend of Climate Change and Drought Assessment in the Horn of Africa - Mihretab G. Ghebrezgabher; Taibao Yang; Xuemei Yang (Advances in Meteorology)
Climate change due to global warming is a world concern, particularly in Africa. In this study, precipitation and temperature variables are taken as a proxy to assess and quantify the long-term climate change and drought in the Horn of Africa (HOA) (1930–2014). We adapted a simple linear regression and interpolation to analyze, respectively, the trend and spatial distribution of the mean annual precipitation and temperature. In addition, standardized precipitation evapotranspiration index (SPEI) was applied to evaluate the drought condition of the HOA. The results revealed that statistically the trend of precipitation decreased insignificantly; the trend of temperature was observed to drop very significantly between 1930 and 1969, but it was dramatically elevated very significantly from 1970 to 2014. The SPEI showed that the HOA experienced from mild to moderate drought throughout the study period with severe to extreme drought in some regions, particularly in 1943, 1984, 1991, and 2009. The drought was a very serious environmental problem in the HOA in the last 85 years. Thus, an immediate action is required to tackle drought and hence poverty and famine in the HOA.